Initial considerations for the creation of an inter-regional industrial hemp value chain between Malawi and South Africa - Sandy Lowitt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Interest in industrial hemp has revived in the past 20 years. Malawi is considering legalizing the cultivation of industrial hemp as an alternative cash crop to tobacco with great potential. This study considers the potential and challenges of creating an industrial hemp value chain between South Africa and Malawi, with Malawi concentrating on upstream cultivation and South Africa on downstream value-adding activity. The research supports a finding that industrial hemp offers strong opportunities as a niche market even if mainstream demand is slow to materialize or does not materialize at all. It also shows that undertaking such an inter-regional endeavour would be considerably more complicated than initially envisaged, given the agricultural structure and operation of the Malawian economy and its smallholder farmers.
Keywords: D1; D4; O13; Q13; 330; contract buying; industrial hemp; novel crop establishment; regional value chain